The improvement students learning achievement by applying work based learning combined with teaching factory concept - Maksum, Hasan; Purwanto, Wawan; Sugiarto, Toto; Hidayat, Nuzul; Siman, Siman; Hasan, Hanapi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The preliminary analysis results indicate that the quality of automotive vocational learning is not optimal. This study aims to develop a work-based learning model that incorporates the Teaching Factory concept (WBL-TEFA) with the goal of enhancing the learning achievement of automotive vocational students. Research and Development (R&D) with the 4D model were implemented in this study. The results indicate that the WBL-TEFA learning model introduced novel elements to the model syntax through the following activity steps: (1) initiation, (2) receiving orders, (3) gathering necessary information, (4) generating and sorting possible solutions, (5) executing orders, (6) quality control, and (7) assessment. To implement this syntax, various supporting materials were developed, including model handbooks, lecturer and student manuals, and textbooks. Following the implementation, the experimental class demonstrated a significantly higher learning achievement gain score of 51.62 compared to the control class, which achieved a gain score of 42.52. Additionally, there was an improvement in task management abilities, work environment skills, interpersonal skills, workplace learning skills, and student critical thinking. In summary, the utilization of the WBL-TEFA learning model proved effective in enhancing students' academic performance, as evidenced by a statistically significant.